Harvesting process is a critical time to identify the quality of raw material for traditional medicine. The time and harvesting techniques, drying process after harvesting, and processing to make the simplicia, are the crucial role to make the good quality of the natural product. On the other hand, there is a lack of general understanding and appreciation about the processes involved in governing shoot and tree growth and development, i.e. red guava. The research objective was to evaluate the i - SANDRA ARIFIN AZIZ; MUNIF GHULAMAHDI (HAYATI Journal of Biosciences, 2011)
Harvesting process is a critical time to identify the quality of raw material for traditional medicine. The time and harvesting techniques, drying process after harvesting, and processing to make the simplicia, are the crucial role to make the good quality of the natural product. On the other hand, there is a lack of general understanding and appreciation about the processes involved in governing shoot and tree growth and development, i.e. red guava.  The research objective was to evaluate the influence of leaf harvesting and growth phases on red guava for flavonoid production as antioxidant. Randomized factorial block design in time were laid out with two factors and followed by Duncan’s multiple range test. The treatments were the amount of leaf  harvested on tertiary branches (0, 25, 50, and 100%) and growth phases of the plant (vegetative and generative). Leaf harvesting 25% on tertiary branches significantly increased the leaf number (766.3 tree-1) and the number of new quarternary branches, decreasing leaf area index (LAI) and leaf dry weight at the end of the experiment (22 weeks of observation/WO).  The highest leaf dry weight (156.94 g tree-1) and LAI (0.47) was found in harvesting 25% tertiary branches.  Harvesting 100% leaf on tertiary branches in vegetative phase significantly produced the lowest flavonoid production (7.82 g tree-1). The result suggested that flavonoid production from red guava leaves should be done by harvesting 50% leaf on tertiary branches in generative phase can be used to produce the highest flavonoid (89.90 g tree-1).